An evaluation of government role in green supply chain management through theories - Nezakati, Hossein; Fereidouni, Meghdad Abbasian; Abd Rahman, Azmawani (EconJournals, 2016)
Companies self-regulating were mostly for improving their reputation and public image rather than achieving to sustainability goals and this let to shift to co-regulating approach. In co-regulation practices, however, NGOs initially played a vital role to reduce the companies’ misuse of self-regulating era, but given that many companies have tied with NGOs and under business-NGOs partnership concealed the corruptions. The aim of this study is to evaluate the role of Governments in Green Supply Chain Management in order to examine the coercive and supportive dimensions of governments’ effects on all stakeholders’ actors. In this regard, stakeholder theory, institutional theory and resource based view have been utilized to identify and explain the governments’ role in the chain. The findings of this research suggested that governments’ stewardship role can be more appropriate to the Green Supply Chain Management in order to coordinate and integrate the supply chain activities. This study has proposed a conceptual model which it can be empirically tested for future studies.